1985
DOI: 10.1083/jcb.100.6.1817
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of zinc in the regulation of pHi, motility, and acrosome reactions in sea urchin sperm.

Abstract: When sperm of Strongylocentrotus purpuratus or Lytechinus pictus are diluted into seawater, motility is initiated; and when exposed to egg jelly, an acrosome reaction is induced. In the presence of a variety of structurally different metal chelators (0.1-1 mM EDTA, EGTA, phenanthroline, dipyridyl, cysteine, or dithiothreitol), motility initiation is delayed and the acrosome reaction is inhibited. Of the metals detected in the sperm of these two species, very low levels of Zn +2 (0.1 /~M free Zn ÷z) uniquely pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
31
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 25 publications
3
31
0
Order By: Relevance
“…Sea urchin sperm are known to initiate their motility when suspended in seawater. According to Clapper et al (1985) The effect of histidine on the motility activation of flagella decreased at the end of the breeding season (data not shown), suggesting that there is an association of Zn 2+ with the maturity of sperm. The effect of EDTA also decreases with maturity in starfish Asterias amurensis (Mohri et al, 1990).…”
Section: Activation Of Flagellar Motility By Histidinementioning
confidence: 99%
See 1 more Smart Citation
“…Sea urchin sperm are known to initiate their motility when suspended in seawater. According to Clapper et al (1985) The effect of histidine on the motility activation of flagella decreased at the end of the breeding season (data not shown), suggesting that there is an association of Zn 2+ with the maturity of sperm. The effect of EDTA also decreases with maturity in starfish Asterias amurensis (Mohri et al, 1990).…”
Section: Activation Of Flagellar Motility By Histidinementioning
confidence: 99%
“…These results suggest (Christen et al, 1982;Lee et al, 1983;Lee, 1985). Zn 2+ is also involved in the regulation (Clapper et al, 1985), but the mechanism of action is different. Sea urchin sperm are known to initiate their motility when suspended in seawater.…”
Section: Activation Of Flagellar Motility By Histidinementioning
confidence: 99%
“…Morisawa and Yoshida have also reported that Zn in the seminal plasma of human suppresses sperm motility, and that the removal of Zn by binding to a protein named semenogelin enhances motility (6). On the other hand, in sea urchin, treatment with the bivalent metal ion chelator, ethylenediamine tetra acetic acid (EDTA), inhibits sperm motility that is reversed by the addition of Zn (9). These results suggest that extracellular Zn indeed affects sperm motility but whether this is inhibitory or stimulatory appears to be species-specific.…”
mentioning
confidence: 99%
“…This solution, which will be referred to as KEG, substantially retards motility initiation in sea-urchin sperm cells as described later on. The idea of retardation by KEG is based on the facts that sea-urchin sperm remain quiescent in Na + -free seawater (Lee et al ., 1983;Bibring et al ., 1984;Schackmann et al ., 1984;Gatti and Christen, 1985;Christen et al ., 1986), and also immotile at elevated K + concentrations (Christen et al ., 1986;Bracho et al ., 1997) and become active when the intracellular pH is elevated, e.g., by addition of Na + or amine (Christen et al ., 1982;Lee et al ., 1983;Bibring et al ., 1984;Lee, 1984a, b;Bracho et al ., 1997), and that activation is, however, delayed in the presence of a variety of metal chelators including EDTA (Clapper et al ., 1985;Christen et al ., 1986). The KEG retardation of motility initiation first revealed distinct transient patterns of flagellar bending described in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Motility initiation involves the switching on of the sperm flagellar apparatus, which occurs simultaneously or successively, probably creating transient states of the axoneme with some mechanisms working but others being suppressed. Motility initiation, however, occurs instantaneously or so rapid that it is hard to capture such transients for analysis, when sperm are diluted in seawater (Clapper et al ., 1985;Dorsten et al ., 1997).…”
Section: Introductionmentioning
confidence: 99%